2012
DOI: 10.1007/s11010-012-1340-9
|View full text |Cite
|
Sign up to set email alerts
|

Early cardiovascular changes occurring in diet-induced, obese insulin-resistant rats

Abstract: The metabolic syndrome is recognized as a cluster of disturbances associated with obesity, type 2 diabetes and hypertension. Over the past two decades, the number of people with the metabolic syndrome has increased at an alarming rate. This increase is associated with the global epidemic of both obesity and diabetes. Cardiovascular mortality is increased among diabetics and obesity-related insulin-resistant patients, and obesity is currently recognized as independent risk factor for cardiovascular disease. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 36 publications
6
18
2
Order By: Relevance
“…Since hyperglycemia activates the cardiac intracellular renin-angiotensin system, which increases oxidative stress and cardiac fibrosis [36], the absence of hyperglycemia in our model could explain the preservation of function and heart morphology. Different experimental studies have previously shown that obese, dyslipidemic and insulin resistant mice are more prone to acute ischemia/reperfusion injury [13][14][15][16]37]. However, our results reveal that HFD-induced obesity paradoxically reduces ventricular dilatation, dysfunction and infarct size after transient coronary occlusion.…”
Section: Discussioncontrasting
confidence: 56%
“…Since hyperglycemia activates the cardiac intracellular renin-angiotensin system, which increases oxidative stress and cardiac fibrosis [36], the absence of hyperglycemia in our model could explain the preservation of function and heart morphology. Different experimental studies have previously shown that obese, dyslipidemic and insulin resistant mice are more prone to acute ischemia/reperfusion injury [13][14][15][16]37]. However, our results reveal that HFD-induced obesity paradoxically reduces ventricular dilatation, dysfunction and infarct size after transient coronary occlusion.…”
Section: Discussioncontrasting
confidence: 56%
“…This agrees well with results obtained ex-vivo [5][6][7] and in-vivo [4,8,9] in rats fed a HF diet. However, this is in total opposition with the results from ZDF rats [13,14] and SMC-fed animals [2,3]. Yet, the two last situations are associated with increased blood glucose, whereas the increased chow intake was not in our study.…”
Section: Cardiac Function During Ischemia/reperfusioncontrasting
confidence: 99%
“…Thirdly, IAA is associated with low-grade inflammation [49], which could also have played a role. In spite of these environmental differences, several studies [2][3][4][5][6][7][8][9] have shown that the response to ischemia/reperfusion was similar in both in-vivo and exvivo contexts.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This difference was still present after 17 months, although aging per se also caused a significant increase in intraperitoneal fat in the age-matched controls. We have previously demonstrated that the diet induced insulin resistance associated with a significant rise in serum insulin but not glucose levels [38]. …”
Section: Discussionmentioning
confidence: 99%